2016
DOI: 10.5455/apd.172823
|View full text |Cite
|
Sign up to set email alerts
|

Oxybutynin addiction amongst prisoners: two case reports

Abstract: This study was designed to present two inmates staying Konya E type prison and wanting to increase the prescripttion and/or current dosages of oxybutynin. The study showed that oxybutynin is used to achieve similar feelings to the effects obtained by the use of substance and alcohol among inmates. Mahkumlar arasında oxibutinin bağımlılığı: İki olgu sunumu ÖZBu çalışma Konya E tipi cezaevinde kalan ve oxibutinin kullanan veya kullandığı oxibutininin dozunu artırmak isteyen iki mahkumu sunmak için planlandı. Çal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…In many of these studies, it was reported that the costs of individuals with alcohol or substance use disorders to society increase due to both their involvement in crime and substance use [21][22][23]. From another point of view, in research on prisoners, a history of addiction and prescription drug abuse in prison was shown [24,25]. Our results supported the literature data.…”
Section: Discussionsupporting
confidence: 89%
“…In many of these studies, it was reported that the costs of individuals with alcohol or substance use disorders to society increase due to both their involvement in crime and substance use [21][22][23]. From another point of view, in research on prisoners, a history of addiction and prescription drug abuse in prison was shown [24,25]. Our results supported the literature data.…”
Section: Discussionsupporting
confidence: 89%
“…A case series reported on the oxybutynin misuse in two male subjects aged 27 and 45 years, both diagnosed with a SUD, who orally took 100–150 mg/day and 300–400 mg/day of the drug, respectively [ 54 ].…”
Section: Resultsmentioning
confidence: 99%